Tra habitat e habitus. Classi borghesi e cultura materiale in Africa meridionale - Di Fiore, Laura; Mari, Lorenzo (Status Quaestionis, 2017)
Analysing the rise of Southern African middle classes as a specific case study, the aim of this paper is to emphasize the plural and entangled histories of black middle classes within two national contexts. The analysis of the dichotomy between the white rural middle class (as especially recognizable in the history of South African Boers) and the black urban Lumpenproletariat as structuring the political and cultural history both of South Africa and Zimbabwe, in fact, is eventually challenged by the rise of black middle classes in the postcolonial and post-apartheid era. As these processes are rooted in a peculiar habitat such as the farm and exerted through a specific and yet all-encompassing habitus, this paper will retrace these aspects in the history of Southern African literature in English, focusing on recent novels such as John Maxwell Coetzee’s Disgrace (1999) and Peter Godwin’s When A Crocodile Eats The Sun (2006).